B Cells Specific CpG Induces High IL-10 and IL-6 Expression In Vitro in Neuro-Behçet’s Disease - Olfa Maghrebi; Meriam Belghith; Cyrine Jeridi; Amine Rachdi; Fatma Nabli Fatnassi; Zakaria Saied; Samir Belal; Samia Ben Sassi; Mohamed-Ridha Barbouche (Cells, 2022)
Remitting-RelapsingMultiple Sclerosis (RRMS) and Neuro-Behçet Disease (NBD) are two chronic neuroinflammatory disorders leading to neurological damage. Herein, we investigated in these patients the IL-10-producing cells during the early stages of these disorders. Cellular and molecular investigations were carried out on treatment naive patients suffering from RRMS and NBD recruited at the first episode of clinical relapse. Our findings demonstrate that CSF-B cells from NBD patients, but not RRMS, are the major source of intrathecal IL-10 as compared to T-CD4 cells. Moreover, we showed a lower expression of TGF-β and IL35, in the CSF cells of NBD patients as compared to the control group. Specific in vitro CpG stimulation of peripheral blood B cells from NBD patients resulted in a concomitant early mRNA expression of IL6 and IL10 but was limited to IL10 for RRMS patients. Furthermore, mRNA expression of IL-6 and IL-10 receptors was assessed and intriguingly IL6ST receptor subunit was significantly lower in NBD CSF, but not RRMS while IL10RB was increased in both. Deciphering the role of increased IL-10-producing B cells and IL10RB despite relapsing disease as well as the discordant expression of IL6 and IL6ST may pave the way for a better understanding of the pathophysiology of these neuro-inflammatory disorders.